FASCIAL SLINGS: A NEW ADJUNCT TO BRACHIOBASILIC FISTULA ELEVATION - Hafiz Khalid Pervaiz Butt (Army Medical College Rawalpindi, 2018)
Objective: To introduce a new technique of fascial slings created from fascia over biceps muscle as an adjunct to Brachiobasilic fistula elevation contributing in the ease of cannulation and position of arm for both nursing staff and the patient. Study Design: Retrospective study. Place and Duration of Study: This study was carried out in Combined Military Hospital Rawalpindi, form Jan 2016 to Apr 2017. Patients and Methods: The demographic and outcome data of the patients, who underwent Brachiobasilic Elevation using fascial slings, were collected and analyzed retrospectively. Results: A total of 89 (60 males, mean age 44.2 ± 14 years and 29 females mean age 42.6 ± 12 years) patients underwent brachiobasilic fistula elevation. The distance of fistula vein from skin incision at mid arm was found to be consistent from the per op measurement till the last assessment at 6 months. In our study it was 5 ± 0.7 cm. Slinged vein was found to be easy to cannulate in first prick as per dialysis nursing staff. Fistula maturation rate was 91%. A total of eight (9%) fistulae were never put on dialysis because of thrombosis. The mean maturation time was 40 ± 14 days. Fifteen (16%) patients had arm edema, and twelve (13%) had infections. Patients had similar ease of arm position as of brachiocephalic AVF during dialysis. Conclusion: Considering the consistent post op distance of fistula vein from scar site, ease of cannulation for the dialysis staff and comfort of arm position for the patient during dialysis after fascial slings it is concluded that fascial slings are good adjunct to basilic vein elevation technique.